Hubungan antara diagenesis, reflektan vitrinit, dan kematangan batuan pembawa hidrokarbon batuan sedimen Miosen di Cekungan Bengkulu - Rachmat Heryanto (Indonesian Journal on Geoscience, 2007)
http://dx.doi.org/10.17014/ijog.vol2no2.20074The Early-Middle Miocene Seblat and Middle-Late Miocene Lemau Formations are two of sedimentary rock lithstratigrphic unit that occur in the Bengkulu Basin. Lithologically, the Seblat Formation consists of mudstone with some interbedded sandstones and conglomerate in the lower part and tuffaceous mudstone with some limestone lenses in the upper part. The Lemau Formation, however, comprises dominant sandstones with interbedded shales and sub-ordinate conglomerates and mudstone beds in the lower part, and mudstone with sandstone intercalations and coal seams in the upper part.Hydrogen Index (HI) versus Temperature Maximum (T) diagram shows that the source rock maturation at most of the samples is late immature to early mature. The vitrinite reflectance the dispersed organic matter (DOM) ranges from 0.37 to 0.55%; whereas of the coal seam ranges from 0.76 up to 0.94%. This indicates that the source rock maturation is defined to be late immature to early mature. The data indicate a burial history for about 2,500 m in depth, where the paleotemperature reached 80o C.Diagenetic processes observed from the Seblat and Lemau Sandstones are compaction, the forming of authigenic minerals and secondary porosities. The diagenetic stage includes the mesogenetic mature A, which equivalent to mudrock stage II, with the paleotemperature of 80o to 95o C, and the burial thickness of 2 to 3 km.There is a relationship between diagenetic stage, vitrinite reflectance, and maturation of organic matter of hydrocarbon source rock, caused by the burial depth.